Rancang Bangun Aplikasi Pemesanan Dan Penjualan Berbasis E – Commerce Pada Produk UMKM Desa Kiringan Kabupaten Magetan (Studi Kasus: Ds. Kiringan Kec. Takeran Kab. Magetan) - Pratama Tegar Al Hafizh (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2022)
The advancement of information technology is currently growing rapidly,especially the development of the internet has become a necessity to findinformation. The use of the internet allows everyone to easily carry out the processof buying and selling online known as "e-commerce". In UMKM of Kiringan Villagethere are chicken egg breeders numbering 28 breeders. One of the producers in thisstudy provided two types of chicken eggs, namely red chicken eggs and kampungchickens with a production of 2,450 eggs per day. The problem is that chicken eggssold have never been marketed online, so consumers do not know much about theexistence of chicken eggs in Kiringan Village. With this problem, the owner of achicken egg UMKM needs a marketing information system in the form of a website.In this study poured the idea to design an information system in the form of awebsite using the waterfall method to expand market share in order to increaseincome in chicken egg UMKM, The delivery process also uses a special containerof anti-breakible eggs that are good so that on the go when shipping no eggs arebroken, and also support the marketing of Chicken Egg UMKM in MagetanRegency. Effectiveness is supported by internet technology to market productsthroughout the magetan region, in order to improve the economy of UMKM owners.Keywords: Website-based applications, Waterfall, UMKM, Sales, E-commerce